Faktor-Faktor Yang Berhubungan dengan Persalinan Prematur - Ida Rahmawati; violita siska mutiara; Nuril Absari; Putri Andini (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2021)
Premature labor is labor before 37 weeks' gestation or birth weight between 500-2499 grams. The impact of premature birth is likely that babies born prematurely will need intensive care to survive. This study aims to study the factors associated with preterm labor in the Rose Room of RSUD Dr. M. Yunus Bengkulu in 2018. The study used the Analytical Survey method with a Case Control design. The population is all maternity mothers in the RSUD dr. M. Yunus Bengkulu in 2018 as many as 603 deliveries. Samples were taken as many as 88 mothers consisting of 44 mothers with preterm labor taken by Total Sampling and 44 mothers without preterm labor who were taken by Systematic Random Sampling. The data used is secondary data. Data were analyzed using univariate, bivariate and multivariate analysis with Chi Square (c2) and Contingency Coefficient (C) tests. The results obtained from 88 mothers there were 44 (50.0%) mothers with preterm labor, 44 (50.0%) non-preterm delivery mothers, 61 (69.3%) mothers aged 20-35 years, 52 (59.1 %) multiparous parity mothers, 61 (69.3%) mothers not KPD, there is an age relationship with preterm labor with the category of moderate relationship, there is a relationship of parity with preterm labor with a close relationship category, there is a relationship of KPD with preterm labor with a close relationship category. It is hoped that health workers can increase screening for pregnant women who visit the Midwifery Clinic to conduct early detection of pregnancy at risk so that it does not have an impact on preterm labor.